A handbook of wisdom psychological perspectives - Sternberg, Robert J.; Jordan, Jennifer 1982- (Cambridge University Press, 2005)
A topic ignored in mainstream scientific inquiry for decades, wisdom is beginning to return to the place of reverence that it held in ancient schools of intellectual study. A Handbook of Wisdom, first published in 2005, explores wisdom's promise for helping scholars and lay people to understand the apex of human thought and behavior. At a time when poor choices are being made by notably intelligent and powerful individuals, this book presents analysis and review on a form of reasoning and decision-making that is not only productive and prudent, but also serves a beneficial purpose for society. A Handbook of Wisdom is a collection of chapters from some of the most prominent scholars in the field of wisdom research. Written from multiple perspectives, including psychology, philosophy, and religion, this book gives the reader an in-depth understanding of wisdom's past, present, and possible future direction within literature, science, and society